The research stands on the basis of the typical gamma-spectrometric complex - Поп, Оксана Михайлівна; Стець, Михайло Васильович; Маслюк, Володимир Трохимович (Eastern-European Journal of Enterprise Technologies, 2014)
Multifunctionality of typical gamma-spectrometric complexes, which should solve various tasks of applied nuclear gamma-ray spectrometry is considered. These tasks include: - defining nuclide and element composition of matter; - developing the system for determining metrological registration factors of gamma-radiation of bulk samples; - developing the background stabilization and reduction system; - developing the internal security system. The description of the developed and existing research stands that solve these tasks at the gamma-spectrometric complex of the Institute of Electron Physics of the NAS of Ukraine is given. It is shown that these systems act as autonomous research stands that typically exist as independent units. The fact of efficiency of multifunctionality of gamma-spectrometric complex allows to conclude on the possibility to implement functional completeness in the gamma-spectrometric complex as a system. Operation of research stands allows to make the process of improving gamma-spectrometric complex indicators in whole and in specific cases constant. Results are related to typical gamma-spectrometric complexes, which are in the majority. Therefore, our results can be used in practice in many analytical laboratories.